Relationships of Demographic and School Related Variables to Curriculum Improvement Skill Scales for Graduating Business (Journal of Education and Development, 2022)
Business schools continue to monitor student perceptions of their curriculum during the ongoing pandemic. 274 graduating business seniors filled out a Spring 2022 exit survey asking their perceptions about the business school’s curriculum improving their abilities on twelve goals. A factor analysis of these twelve individual items resulted in keeping all items and creating three smaller scales (items/scale): Business Problem Solving (6 items), Presentation Skills (3 items) and Team-related Skills (3 items). These three scales were found to be reliable and sufficiently distinct from each other. Overall, students perceived that the business school’s curriculum improved their team-related skills significantly more than business problem solving and presentation skills. Grade Point Average or gender were not related to any scale improvement differences. Paired t-test results included finding that transfer students indicated significantly higher improvement on business problem solving and team-related skills than non-transfer students. In addition, non-quantitative majors showed higher improvement on presentation skills than quantitative majors. A stronger baseline for these three curriculum improvement scales has now been established for follow-up monitoring. Results are further discussed.